2005
DOI: 10.1128/iai.73.9.5395-5401.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Heparan Sulfate Promotes Replication of Toxoplasma gondii

Abstract: Previous work suggests that cell surface heparan sulfate acts as a receptor for the Apicomplexan parasite Toxoplasma gondii. Using Chinese hamster ovary cell mutants defective in heparan sulfate biosynthesis, we show that heparan sulfate is necessary and sufficient for infectivity. Further, we demonstrate that the parasite requires N sulfation of heparan sulfate initiated by N-deacetylase/N-sulfotransferase-1, but 2-O sulfation and 6-O sulfation appear to be dispensable. In order to study the role of heparan s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 55 publications
1
11
0
1
Order By: Relevance
“…This idea is further supported by the finding that treatment of HCT-8 cells with heparinase II, ␤-xyloside, or sodium chlorate reduced C. parvum infection more than attachment alone. Proteoglycans have been implicated in the mediation of intracellular development of T. gondii as well (41). Similar to CpClec-Fc, C. parvum attachment to CHO pgsA-745 and pgsD-677 was comparably reduced, a finding also reported for T. gondii (21), suggesting that intestinal apicomplexan parasites display a higher affinity for HSPGs during infection.…”
Section: Discussionsupporting
confidence: 60%
“…This idea is further supported by the finding that treatment of HCT-8 cells with heparinase II, ␤-xyloside, or sodium chlorate reduced C. parvum infection more than attachment alone. Proteoglycans have been implicated in the mediation of intracellular development of T. gondii as well (41). Similar to CpClec-Fc, C. parvum attachment to CHO pgsA-745 and pgsD-677 was comparably reduced, a finding also reported for T. gondii (21), suggesting that intestinal apicomplexan parasites display a higher affinity for HSPGs during infection.…”
Section: Discussionsupporting
confidence: 60%
“…In the glucuronosyltransferase-deficient CHO cell line, Toxoplasma replication is retarded (42). In the clones that we obtained, we observed no deficiency in the ability of Chlamydia to replicate in the null clones once access was gained, notwithstanding the deficit in attachment.…”
Section: Discussionmentioning
confidence: 55%
“…The initial binding to a negatively charged component of the membrane is mediated by the net positive charge of each GRA2 amphipathic α-helix. Although the binding of GRA proteins to the heparan sulfate structure has never been investigated, it was reported that heparan sulfate facilitates the replication of T. gondii in the parasitophorous vacuole (Bishop et al 2005). However, it is logical that the most important binding event occurs during the initial contact between the tachyzoite and the host cell and is, in part, mediated by the tachyzoite SAG family of surface protein and host cell proteoglycans.…”
Section: Discussionmentioning
confidence: 98%